Utilization Experiential Learning for Increase Quality Character Development of Child's Language in Communication Verb - Yani Supriani; Usep Sholahudin; Giyanti (Jurnal Pendidikan Anak Usia Dini Undiksha, 2022)
Language character of students is the lack of verbal communication between students educate one with other, child still quiet type and seldom communicate direct with friend his age. Media experiential learning trusted be able to grow flavor believe self child and interest child in initiate direct communication with their peers. This study aims to analyses the application of experiential learning based on preloved (used goods) for students' linguistic abilities. The method used in this research is a phenomenological approach. This research was conducted on children in group A in one of the kindergartens involving 16 children in total. This research is a classroom action research, the problems studied will be solved through the use of experiential learning. The data collection methods used are observation, interviews and experimental studies. The results of this study found that through the use of experiential learning can improve language skills especially in communicate by direct (verbal) on child group A in one of the kindergartens. It is indicate the effectiveness of the experiential implementation learning in improving the quality of children's language character development in verbal communication.